HOUSING AND CONSTRUCTION COOPERATIVES IN PORTUGAL. STATE-OF-THE-ART AND LINES OF REFORM - Meira, Deolinda (International Journal of Cooperative Law, 2024)
In Portugal, housing and construction cooperatives are governed by the provisions of Decree-Law no. 502/99 of 19 November and, in the absence of such provisions, by the provisions of the Cooperative Code, which was extensively modernised in 2015. The sectoral legislation on housing and construction cooperatives needs to be reformed, taking into account the innovations introduced in the revision of the Cooperative Code. In this future revision of the sector’s legislation, two fundamental aspects must be taken into account. With regard to operations with third parties, the obligation to consider such operations as complementary should be eliminated. Of particular note is the need to review the classification of the act of transferring housing under the individual property regime, changing the solution provided for in current legislation, which qualifies this act as a purchase and sale. The adjudication regime is the most appropriate solution for this act of transfer.